Impact Investigation of Stator Seal Leakage on Aerodynamic Performance of Multistage Compressor - Wang, Qi; Zhang, Zhou; Hong, Qingsong; Ren, Lanxue (Frontiers in Energy Research, 2021)
This paper presents a numerical model based on the mass flow rate of seal leakage and a 3-D numerical method which has good engineering practicability for multistage axial compressor is set up on the basis. Validation consists of modelling a nine-stage axial compressor in all operating rotation speeds, calculating results of the performance characteristic curves with good agreement to test data. Comparisons are made against different cases of seal leakage mass flow rate for analyzing the impact of seal leakage increasing on the aerodynamic performance of multistage axial compressor. The results indicate that performance of the nine-stage axial compressor is degenerated faster and faster with seal leakage increasing in all operating working points, and the degeneration of performance for this compressor can be evaluated by the relationships of main performance parameters with the mass flow rate of seal leakage. Comparisons of flow distribution in the compressor for different cases of seal leakage also show that stators located in front stages of multistage axial compressor are affected more seriously by the seal leakage increasing, and it can be confirmed that relatively larger flow losses in front stages bring significant impact on the decay of aerodynamic performance for a multistage axial compressor.